A desferrioxamine B squaramide ester for the incorporation of zirconium-89 into antibodies. Issue 80 (30th August 2016) - Rudd, Stacey E.; Roselt, Peter; Cullinane, Carleen; Hicks, Rodney J.; Donnelly, Paul S.
Abstract : A squaramide ester derivative of desferrioxamine B is used to attach zirconium-89 to the antibody trastuzumab and the new conjugate is used for positron emission tomography imaging in mouse models of breast cancer. Abstract : A squaramide ester derivative of desferrioxamine B (H3 DFO) that is compatible with aqueous solvents and does not induce antibody aggregation is used to attach the siderophore to the antibody trastuzumab. The new conjugates were radiolabeled with zirconium-89 to give complexes that are more resistant to ligand exchange when compared to currently used H3 DFO derivatives and result in high quality positron emission tomography images in mouse models of HER2 positive breast cancer.